The Biotech Motherhood and the missing speech - Colombetti, Elena (Medicina e Morale, 2022)
The arrival at the question of surrogacy is the outcome of a cultural and technical process that has also led to look at technoscience as a privileged instrument of women's liberation, breaking what was seen as an oppressive alliance between nature and culture. In particular, liberation from motherhood, understood by radical feminism as a condemnation, has turned into liberation of motherhood, inserting it into the controlled dimension of the project. In these pages, we propose to address the issue of surrogacy from the perspective of women, testing the veracity of this reading of the combination technoscience-liberation. We will do it starting from some feminist readings that give a philosophical voice, not simply testimonial, to the lived or otherwise possible pregnancy experience. They also state the theme of expressibility and oblivion of the maternal genealogy.